Association between diet and polymorphisms in individuals with statin-controlled dyslipidaemia grouped according to oxidative stress biomarkers - Patrícia Borges Botelho; Cyntia Okoshi Fioratti; Marcelo Macedo Rogero; Lucia Pereira Barroso; Marcelo Chiara Bertolami; Inar Alves Castro (Universidade de São Paulo, 2012)
The objective of this study was to investigate whether differences in diet and in single-nucleotide polymorphisms (SNPs) found in paraoxonase-1 (PON-1), 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR), cholesterol ester transfer protein (CETP) and apolipoprotein E (APOE) genes, are associated with oxidative stress biomarkers and consequently with susceptibility of low-density cholesterol (LDL) to oxidation. A multivariate approach was applied to a group of 55 patients according to three biomarkers: plasma antioxidant activity, malondialdehyde and oxidized LDL (oxLDL) concentrations. Individuals classified in Cluster III showed the worst prognoses in terms of antioxidant activity and oxidative status. Individuals classified in Cluster I presented the lowest oxidative status, while individuals grouped in Cluster II presented the highest levels of antioxidant activity. No difference in nutrient intake was observed among the clusters. Significantly higher γ- and δ-tocopherol concentrations were observed in those individuals with the highest levels of antioxidant activity. No single linear regression was statistically significant, suggesting that mutant alleles of the SNPs selected did not contribute to the differences observed in oxidative stress response. Although not statistically significant, the p value of the APO E coefficient for oxLDL response was 0.096, indicating that patients who carry the TT allele of the APO E gene tend to present lower plasma oxLDL concentrations. Therefore, the differences in oxidative stress levels observed in this study could not be attributed to diet or to the variant alleles of PON-1, CETP, HMGCR or APO E. This data supports the influence of γ-tocopherol and δ-tocopherol on antioxidant activity, and highlights the need for further studies investigating APO E alleles and LDL oxidation. O objetivo deste estudo foi investigar se diferenças na dieta e em polimorfismos de nucleotídeos únicos (SNPs) encontrados no gene da paraoxonase 1 (PON-1), da 3-hidroxi-3-metilglutaril-coenzima A reductase (HMGCR), da proteína de transferência de ésteres de colesterol (CETP) e da apolipoproteina E (APOE) estariam associadas com biomarcadores do estresse oxidativo e, consequentemente, com a suscetibilidade da LDL à oxidação. Técnicas da estatística multivariada foram aplicadas a um grupo de 55 pacientes usando 3 biomarcadores: atividade antioxidante plasmática, concentrações de malondialdeído e LDL oxidada. Indivíduos classificados no cluster III apresentaram um prognóstico negativo em termos de atividade antioxidante e estado oxidativo. Os indivíduos agrupados no cluster I apresentaram o mais baixo nível de estado oxidativo, enquanto que indivíduos no cluster II apresentaram os mais altos níveis de atividade antioxidante. Nenhuma diferença na ingestão de nutrientes foi observada entre os clusters. Concentrações estatísticamente mais altas de γ- e δ-tocoferol foram observadas em indivíduos com mais altos níveis de atividade antioxidante. A regressão linear aplicada não foi estaticamente significativa, sugerindo que os alelos mutantes dos SNPs selecionados não contribuíram para as diferenças nos níveis de estresse oxidativo. Embora não tenha sido estatisticamente significativa, o valor da probabilidade associado ao coeficiente da relação entre ApoE e oxLDL foi de 0,096, indicando que pacientes que carregam o alelo TT da ApoE tendem a apresentar menores concentrações plasmáticas de LDL oxidada. Portanto, as diferenças no estresse oxidativo observadas em nosso estudo não puderam ser atribuídas à dieta e alelos variantes de PON-1, CETP, HMGCR ou ApoE. Nossos dados suportam a influência γ- tocoferol e δ-tocoferol na atividade antioxidante e reforçam a necessidade de mais pesquisas que investiguem a relação entre alelos da Apo E e a oxidação da LDL.